2007
DOI: 10.1111/j.1556-4029.2007.00500.x
|View full text |Cite
|
Sign up to set email alerts
|

Death in Custody: A Historical Analysis*

Abstract: This research delineates the historical evolution of death in custody. A retrospective, exploratory analysis of 145,425 cases from Maryland's Office of the Chief Medical Examiner, occurring from 1939 to 2004, was conducted. Two hundred and two custodial deaths were identified and subsequently examined relative to time, agency, decedent characteristics, and cause and manner of death. Results indicate that there have been substantive changes in custodial deaths over time. Cardiovascular disease was the most freq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 12 publications
3
25
0
2
Order By: Relevance
“…En nuestro estudio, las muertes naturales representan el 21,9%, cifra más baja que la obtenida por Okoye et al 3 (36%), aunque superior a la hallada por Grant et al 5 en Maryland entre 1990 y 2000 (10%), aunque en este último trabajo hay que tener presente que el 63,5% de las muertes fueron calificadas como indeterminadas. Según Instituciones Penitenciarias, el número de internos fallecidos por causa natural no VIH en el año 2009 fue de 128, con una tasa de 1,9 por cada mil; la mayoría mientras estaban ingresados en centros hospitalarios, y en prisión fallecieron el 41,4%.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…En nuestro estudio, las muertes naturales representan el 21,9%, cifra más baja que la obtenida por Okoye et al 3 (36%), aunque superior a la hallada por Grant et al 5 en Maryland entre 1990 y 2000 (10%), aunque en este último trabajo hay que tener presente que el 63,5% de las muertes fueron calificadas como indeterminadas. Según Instituciones Penitenciarias, el número de internos fallecidos por causa natural no VIH en el año 2009 fue de 128, con una tasa de 1,9 por cada mil; la mayoría mientras estaban ingresados en centros hospitalarios, y en prisión fallecieron el 41,4%.…”
Section: Discussionunclassified
“…En el estudio de Grant et al 5 los homicidios representaron un 8,5%, y en el de Okoye et al 3 un 21%. Según Instituciones Penitenciarias, la mortalidad por agresión en 2009 fue de tres internos, el 1,3% de las muertes en prisión, con una tasa de 0,05 por mil internos; la media de los fallecidos por esta causa en los últimos 10 años es de 2,3 internos por año.…”
Section: Discussionunclassified
“…108 cases of Human Rights Violation by Police were reported out of which 33 were charge-sheeted. 9 A study in Ontario showed 41% natural deaths in custody and in California the same natural deaths was 62% of the custodial deaths. 10,11 Midst custodial deaths, the deaths in prison outstripped the death in police custody.…”
Section: Discussionmentioning
confidence: 99%
“…Less often, suicidal intoxications or completed suicides due to sharp force are observed. Every death in prison or police custody requires an autopsy in which not only suicides, accident-related trauma (sub-or epidural hematomas) and injuries inflicted by another party, but also natural causes of death (such as ischemic heart disease, myocarditis) are detected [54].…”
Section: Suicide In Hospitals In Police Custody or Prisonsmentioning
confidence: 99%
“…Suicides in police custody, pre-trial detention and prison constitute a special category [53,54]. The peak age of this group-composed almost exclusively of males-is reached in the 3rd decade of life.…”
Section: Suicide In Hospitals In Police Custody or Prisonsmentioning
confidence: 99%